Inorganic Nitrogen Enhances the Drought Tolerance of Evergreen Broad-Leaved Tree Species in the Short-Term, but May Aggravate Their Water Shortage in the Mid-Term - Liu, Fangyan; Zhou, Yuheng; Zhang, Shike; Liu, Nan (Frontiers in Plant Science, 2022)
With global climate change, atmospheric nitrogen (N) deposition and drought have been well documented to cause substantial challenges for tropical and subtropical evergreen broad-leaved forests. Here, we conducted an experiment that measured the physiological responses of the seedlings of three dominant tree species (Tabebuia chrysantha, Elaeocarpus sylvestris, and Bischofia javanica) of the evergreen broad-leaved forests in South China under control (CT), drought stress (D), N addition (N), and drought stress plus N addition (N+D). We found that N addition significantly decreased malondialdehyde (MDA) content, abscisic acid (ABA) content, total antioxidant capacity (T-AOC), but significantly increased the content of proline (PRO), and the activities of ribulose-1, 5-bisphosphate carboxylase/oxygenase (Rubisco), nitrate reductase (NR), nitrite reductase (NiR), and glutamine synthetase (GS) in the three species under D. Meanwhile, we also found that under drought conditions, N addition promoted the leaf transpiration rate (E), stomatal conductance (gs), and light-saturated net photosynthetic rate (Amax) of the three species. These results indicate that N addition can enhance the drought tolerance of the three species by osmotic adjustment and protecting the photosystem. However, the enhancement in Amax and E will cause plants to face more severe drought conditions, especially B. javanica (large tree species). This study helps to explain why the evergreen broad-leaved forests in South China are gradually degrading to shrublands in recent decades.